The effects of a globalised agricultural system on South African farm workers : a political ethnographic exploration of Malapeng citrus farm in Limpopo - Goga, Safiyya (University of Pretoria, 2023)
Dissertation (MA (Political Sciences))--University of Pretoria, 2022.